Activating cobalt(II) oxide nanorods for efficient electrocatalysis by strain engineering - Tao Ling (Nature Portfolio, 2017)
The efficiencies of materials-based catalysts are determined by the surface atomic and electronic structures, but harnessing this relationship can be challenging. Here, by engineering strain into cobalt oxide, the authors transform a once poor hydrogen evolution catalyst into one that is competitive with the state of the art.